2015
DOI: 10.1063/1.4921056
|View full text |Cite
|
Sign up to set email alerts
|

Fe-implanted 6H-SiC: Direct evidence of Fe3Si nanoparticles observed by atom probe tomography and 57Fe Mössbauer spectroscopy

Abstract: In order to understand ferromagnetic ordering in SiC-based diluted magnetic semiconductors, Fe-implanted 6H-SiC subsequently annealed was studied by Atom Probe Tomography, 57Fe Mössbauer spectroscopy and SQUID magnetometry. Thanks to its 3D imaging capabilities at the atomic scale, Atom Probe Tomography appears as the most suitable technique to investigate the Fe distribution in the 6H-SiC host semiconductor and to evidence secondary phases. This study definitely evidences the formation of Fe3Si nano-sized clu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 82 publications
1
11
0
Order By: Relevance
“…Theodoropoulou et al showed that 5% of Fe atoms implanted in the 6H-SiC polytype lead to a ferromagnetic material at a temperature of about 250 K. 11 No secondary phase was detected in their samples. Similar findings have been reported by Pearton et al 12 and Stromberg et al 13 Indeed, these authors carried [14][15][16] The formation of nano-sized particles of nano-metric size is partly responsible for the magnetic properties observed on their samples after annealing.…”
Section: Introductionsupporting
confidence: 78%
See 3 more Smart Citations
“…Theodoropoulou et al showed that 5% of Fe atoms implanted in the 6H-SiC polytype lead to a ferromagnetic material at a temperature of about 250 K. 11 No secondary phase was detected in their samples. Similar findings have been reported by Pearton et al 12 and Stromberg et al 13 Indeed, these authors carried [14][15][16] The formation of nano-sized particles of nano-metric size is partly responsible for the magnetic properties observed on their samples after annealing.…”
Section: Introductionsupporting
confidence: 78%
“…Moreover, this Fe 3 Si phase is contained in the biggest nanoparticles included in this sample, as showed in Ref. 15. The magnetic components due to this phase represent (28.3 þ 17.1 ¼ 45.4) of the whole area of this spectrum when the Fs (ferro) component only represents 14%.…”
Section: B 550mentioning
confidence: 99%
See 2 more Smart Citations
“…This phenomenon has been experimentally confirmed; ferromagnetic ordering appears at Curie Temperatures of 50, 250 and 270 K in Ni, Mn and Fe-implanted 6H-SiC [9]. High Curie Temperatures were also achieved in other TM-doped SiC semiconductors [10][11][12][13][14].…”
Section: -2 -mentioning
confidence: 58%